Performance Analysis of a Hardware Solution for Collective Communication Operations on Clusters of PCs - Torres, Martha; Kofuji, Sergio Takeo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2000.41211, 2000)
This paper presents a performance evaluation of a hardware solution for some collective communication operations on a cluster of 8 PCs based on Myrinet and FastEthernet switches. It was implemented a modified version of TTL_PAPERS [DIE 95] for 8 nodes and the hardware collective operations were included in MPICH version 1.1 [GRO 96], which is an implementation of MPI message passing standart. The performance evaluation was done measuring the execution time of the collective operations and evaluating their impact on the total execution time of several applications programs. We concluded the special hardware for collective communication operations is a suitable option to improve the performance on a parallel machine based on cluster of Pcs.